REPRESENTASI PEREMPUAN PADA LUKISAN DI BAK TRUK - Wicandra, Obed Bima (Institute of Research and Community Outreach - Petra Christian University, 2007)
The backs of dump trucks have transformed to not only as a transportation mechanism, but also as visual communication media. This phenomena goes along with the many advertisements that utilizes this kind of medium in promoting certain products. But the backs of dump trucks become a promotional medium because of the already many paintings painted on them, which they are originally plain on the right, left, and the back sides. Women become figures that many portray as their painted subjects. This article focuses more on the painting phenomena that uses the female figures through a gender study, to see whether woman representations in the paintings of the backs of trucks are signified as having imbalanced gender relations. Abstract in Bahasa Indonesia: Bak truk telah menjelma tidak saja menjadi alat transportasi namun juga media komunikasi visual seiring dengan semakin banyaknya iklan yang memanfaatkan media ini dalam mempromosikan suatu produk. Namun perjalanan bak truk menjadi media promosi diawali oleh bertebarannya lukisan yang memanfaatkan bak truk yang semula kosong di sisi kanan, kiri maupun belakang truk. Perempuan menjadi figur yang banyak dipakai sebagai objek lukis. Tulisan ini lebih menyoroti fenomena lukisan yang banyak mengambil figur perempuan dalam kajian gender, untuk melihat apakah representasi perempuan dalam lukisan di bak truk tersebut dimaknai sebagai adanya ketimpangan dalam relasi gender. Kata kunci: representasi, perempuan, bak truk, lukisan, relasi gender.